(untitled) (Biological Sciences - PJSIR, 1994)
Acrylarnide has been graft copolymerized onto casein in phosphate buffer medium. The grafting was characterised by elemental analysis, solubility, FTIR, intrinsic viscosity and refractive index measurements. It was observed that grafting ratio increases with increasing concentration of acrylarnide and decreases with increasing concentration of casein. The effects of concentration of acrylarnide and casein on grafting ratio, grafting efficiency, rate of conversion of monomers and rate of graft copolymerization have been discussed.